Дослідження мети оперативного контролю в контексті кризових умов господарювання - Мельник, Катерина Петрівна; Melnyk, K. P. (Подільський державний аграрно-технологічний університет, 2014)
Проведене комплексне дослідження мети оперативного контролю з врахування циклічних коливань в економіці країни. Критично проаналізовано фундаментальні наукові праці стосовно формування мети управління, мети контролю та мети внутрішньогосподарського контролю. A comprehensive study purpose operational control of the incorporation of cyclical fluctuations in the economy. Critical analysis of fundamental research papers on the formation of management objectives, goals and objectives of internal control monitoring. Based on a detailed assessment of the findings of scientists grouped their views on key criteria for research facilities. Established that an important factor in shaping the purpose of operational control was polity and state-wide processes in the country. We prove that the purpose of operational control is entirely dependent on the objectives of operational management. Recession leads to an increased risk of bankruptcy, loss of competitiveness and a worsening financial situation. The goal of management for profit in such conditions is not satisfied. Therefore, it is not seen as a priority.
Study purpose operational control in the economic crasis conditions
Keywords: мета; управління; контроль; оперативний контроль; кризові явища; економіка; goal; management; control; operational control; crisis; economy